PROGRAM LITERASI MEDIA DI DESA CIBEUREUM KECAMATAN KERTASARI KABUPATEN BANDUNG - Rahman, M. Taufiq; Supratman, Iman; Bukhori, Bukhori (Al-Khidmat : Jurnal Ilmiah Pengabdian Kepada masyarakat, 2019)
The program was carried out to provide media literacy training for the community of Cibeureum Village, Kertasari District, Bandung Regency. There are several objectives to be achieved in this activity, among others: it is expected to be able to add insight into the public about mass media and social media, improve the knowledge and capabilities of media literacy in rural communities. Media literacy training in Cibeureum Village, Kertasari District, Bandung Regency uses training, lecture, discussion, question and answer and case simulation methods. The conclusions obtained from this media literacy training activity are that people can prioritize maturity in choosing which media to consume, content that is responsible even to the point of being able to criticize media content more intelligently.